Electrochemical sensor for ascorbic acid based on zinc oxide nanostructures - Paltusheva, Zh.U.; Gritsenko, L.V.; Kedruk, Y.Y.; Abdullin, Kh.A.; Aitzhanov, М.B.; Kalkozova, Zh.K. (Recent Contributions to Physics, 2023)
Nanostructured semiconductor ZnO and ZnO-GO samples were synthesized at room temperature by chemical bath deposition technique. In this work, the electrochemical non-enzymatic determination of ascorbic acid was studied using the grown nanostructures deposited on a glassy carbon electrode. The morphology and structural properties of the synthesized nanostructured materials were analyzed using a scanning electron microscope and an X-ray diffractometer. The electrochemical properties were studied by the methods of cyclic voltammetry using a single-channel potentiostat-galvanostat. The sensitivity of the obtained electrodes was calculated based on concentrations of ascorbic acid in phosphate buffer solution from 0.3 mM to 3 mM at various scanning speeds. Thus, it was found that the sensitivity of the ZnO-GO sample is lower than that of the ZnO sample, which may be due to the dielectric properties of graphene oxide. However, after annealing in the atmosphere, the sensitivity of the ZnO-GO sample increased, which is associated with a decrease in defects in the sample and an increase in the specific surface area of the samples. As a result of the research, a modified ZnO-GO/GCE electrode with a high sensitivity of 386 μAM-1cm-2 was created, which is promising for use as the basis of a biosensor for determining the level of vitamin C in blood, food, and drugs.